(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2014)
The present study was planned to evaluate the anti-nociceptive, gastro intestinal motility, anti-pyretic and acute toxicity studies of leaf extract of Polygonum hydropiper leaves in albino mice following oral administration. The results showed that the anti-nociceptive activity in the scale of ethanol > n-hexane > petroleum ether > chloroform > methanol extract showed a significant result compared to diclofenac sodium. Chloroform extract showed significant results on gastro intestinal motility test. Ethanol & chloroform extracts showed considerable reduction of temperature at higher doses within 1st hour on yeast induced pyrexia in albino mice. Highest dose introduced as 1000, 2000 & 4000 mg/kg body weight of each extracts in acute toxicity test did not shown any sign of toxicity in albino mice in one week observation. Dhaka Univ. J. Pharm. Sci. 12(2): 165-169, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17619